HYPEREMESIS GRAVIDARUM - M. Tadayon; P. Abedi (Iran University of Medical Sciences, 2004)
Hyperemesis gravidarum is a rare condition that occures about one in 500 Pregnancies. Weight lose, ketoacidosis and serum electrolytes imbalance may occure as the result of hyperemesis. Meanwhile the cause is unknown, some factors such as high HCG level transiant hypothyroidism psychological instability are said to be responsible. Furthermore, the researchers have found some relations between hyperemesis and helicobacter pylori infection. various methods are used to treat hyperemesis such as accupuncture hypnosis and gingers root .